THE EFFECT OF MARKETING STRATEGY AND PROMOTION ON SALES VOLUME, AT TOYOTA AUTO TIMOR-LESTE COMPANY - Guterres, Alexandre de sousa; Freitas , Joao da Costa (Multifinance, 2024)
This study aims to analyze the effect of marketing and promotion strategies on sales volume at Toyota Auto Timor-Leste. This study used quantitative and qualitative approaches, with a descriptive and analytical design. The research sample consisted of 100 customers who had made a purchase in the last 12 months and 10 company managers, who were purposively selected. Data were collected through questionnaires and in-depth interviews and then analyzed using descriptive statistical methods and linear regression to test the relationship between variables. The results show that there is a significant influence between marketing strategies, which include product, price, place, and promotion, on increasing sales volume. In addition, effective promotions through advertisements and special offers are proven to increase consumer appeal. This research provides important insights for the management of Toyota Auto Timor-Leste in formulating better marketing strategies to increase sales in a competitive market. Thus, this research contributes to the understanding of marketing dynamics in the automotive industry in Timor-Leste.